MENINGKATKAN MINAT BELAJAR MELALUI MODEL PEMBELAJARAN WORD SQUARE PADA MATA PELAJARAN AKHLAK - Dadang Sahroni; Sulmiana; Rachma Zahra Nuraqila; Rika Rahman; Septy Premitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning interest is a crucial factor in successful learning, reflected in student concentration and enthusiasm. Low learning interest can be influenced by the inappropriate use of learning models. Therefore, a learning model appropriate to student characteristics is needed, one of which is the word square model. This study aims to determine the application of the word square model, the level of student learning interest, and the model's influence on learning interest in the subject of Aqidah Akhlak for seventh grade at MTs Al-Jamii'ah, Cidolog District, Sukabumi Regency. This study used a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The study sample consisted of 72 students divided into an experimental class and a control class. Data analysis techniques included descriptive statistics, normality tests, homogeneity tests, and hypothesis testing using independent sample t-tests and simple linear regression. The results showed a significant effect of the word square model on student learning interest, indicated by a higher average score in the experimental class compared to the control class (76.86 > 68.14) with a significance level of 0.000 < 0.05. This model contributed 55% to increasing student learning interest.